Unethical Behavior and Group Identity in Contests - Julien Benistant; Marie Claire Villeval (Institute of Labor Economics (IZA), 2019)
Using a real-effort experiment, we study whether group identity affects unethical behavior in a contest game. We vary whether minimal group identity is induced or not, whether individuals have to report their own outcome or the outcome of their competitor, and whether pairs of competitors share the same group identity or not. We show that individuals misreport in the same proportion and to the same extent by inflating their outcome or by decreasing their opponent's outcome, except when any possible scrutiny by the experimenter is removed. Regardless of the possibility of scrutiny by the experimenter, misreporting is affected neither by the competitor's group identity nor by the individual's beliefs about others' misreporting behavior. This suggests that in competitive settings, unethical behavior is mainly driven by an unconditional desire to win.
Keywords: C92; M54; D63; 330; experiment; contests; group identity; sabotage; lying